PEMBERDAYAAN PAGUYUBAN BATIK PENDOPO DESA JARUM BERBASIS KOMUNIKASI PEMASARAN VIRTUAL DI ERA PANDEMI COVID-19 - Puji Lestari; Titik Kusumantini; Elisabet Isyana Rahayu; Devi Wening Astari; Muhammad Irfan (Dharma: Jurnal Pengabdian Masyarakat, 2021)
Virtual marketing communication is still something new for the Paguyuban Batik Pendopo Desa Jarum. Marketing is usually done only through word of mouth and occurs offline. However, due to the COVID-19 pandemic, tourist visits to Jarum Village have greatly decreased. Virtual-based marketing communications are needed to survive in this uncertain situation. With an association that accommodates UMKM, the potential to switch from conventional marketing communications to virtual marketing communications is very high. This service stage starts from discussions with community members of Paguyuban Batik Pendopo Desa Jarum, understanding community members about the importance of virtual marketing communication, assistance in making profile videos, assistance in making websites and blogs, and assistance in creating e-commerce accounts. The contribution made in this service is the assistance of the Paguyuban Batik Pendopo Desa Jarum in virtual marketing communications, especially in the era of the COVID-19 Pandemic.